SELF MANAGEMENT MAHASISWA AKHIR STAI ATTANWIR YANG SUDAH MENIKAH DALAM MENYELESAIKAN TUGAS AKHIR - Siti Puji Utami; Indah Fajrotuz Zahro (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the self-management of final students at STAI Attanwir who are married in completing their final assignment. This study uses a phenomenological qualitative research method. The population in this study were STAI Attanwir students who were married as many as 27 students and with the simple random sampling technique, 15 students were determined as the primary data source. While secondary data sources were obtained from 4 students, journals and documentation. This researcher uses structured interview methods, non-participant observation, and documentation. Data analysis techniques developed by Miles & Huberman. While the validity of the data in this study uses triangulation. The research results obtained show that there are four factors that influence the self-management of STAI Attanwir students who are married in completing their final assignment, namely healthy factors, skills, action and identity. The most influential factor in self-management in completing the final assignment is identity, where by knowing their role as a student, students will complete their final assignment by dividing the roles they play daily. While there are four aspects that influence the self-management of STAI Attanwir students who are married in completing their final assignment, namely self motivation, self organization, self control, and self development. The aspect that most influences is self-development. Where students realize that self-development can support the career that they are currently or will have after graduating from college, in addition to the usefulness of the knowledge they gain in lectures for their role as wives and mothers.